Altitudinal Variation and Aspects Impact on Seed Viability and Germination of Pinus wallichiana in the Nursery - Kaur, Amanpreet; Monga, Rajesh; Bhardwaj, D.R. (Indian Forester, 2024)
The study was carried out on seed viability and germination characteristics of Pinus wallichiana seeds. Seeds were collected from four different altitudinal ranges such as, 1800-2100 (A1), 2100-2400 (A2), 2400-2700 (A3), > 2700(A4) msl and three different aspects namely, southern aspect (As1), eastern aspect (As2), and south-eastern aspect (As3) of Himachal Pradesh. The nursery was raised in the Department of Silviculture and Agroforestry forest nursery at Dr. Y.S. Parmar University of Horticulture and Forestry, Nauni in year 2020. Significant results were observed in the studied parameters; maximum seed viability was obtained at A altitude (75.5%). The 1 germination capacity (90.6%), germination percentage (84.3%), germination energy (32.7%), germination speed (3.42), and germination value (14.5) were all the highest in the southern aspect and on A (1800-2100) altitude, followed 1 by the south-eastern aspect. The correlation analysis revealed that all of the attributes had a negative correlation with altitude and regression analysis 2 showed highest adjusted R value (0.73) in germination value. According to the findings it is suggested that seeds obtained from lower altitudes were acceptable for use in large-scale planting owing to their higher vitality and overall great health.